(3efGXQI Qcf GdOhdI eY GdTjN GdUOhbs - (3GdOQjSJj, GHh YHO Gddg, GdOQjSJj, LYaQ Hf eMeO Hf CMeO GdOhQjSJj, cGf MjG bHd (B460(3g` (B1068(3es ((3GdeTgO GdZQhejs)
(3ChdgG (B:s
(3ChdgG(B: (3GdMeO ddg QH GdYGdejf (B... (3agPg efGXQI Gdedc Qcf GdOhdI dCHj LYaQ GdUOhb Hf HGHhjg Gdbej, bGd Gdedc(B: (3CjgG GdTjN GdYGde GNJda GdMGVQhf aj Gdbhe GdPjf JWYf Ydjge GdTjYIs
(3BNQgG (B:s
(3BNQgG(B: (3hcGf chSi MjK bGd(B: (3QH dG Cedc EdG faSj hGNj(B. (3bGd(B: (3ade RhL YeQ Hf GdNWGH GHfJg? bGd(B: (3dEXgGQ GdTgGOJjf hEbQGQg HaVd QShd Gddg hbO YQV HfGJg Ydi bhe hge caGQ adG HCS aj Pdc(B. (3hGdMeO ddg hMOgs
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf , L (B1: 494s
(3GdPQjYI, L (B22: 184s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3GdJhMjO hGdedd hGdfMds